Screw lateral restraint behaviour of timber and polymeric based railway sleepers. (September 2022) - Yu, Peng; Manalo, Allan; Ferdous, Wahid; Salih, Choman; Heyer, Tom; Schubel, Peter
Graphical abstract: Highlights: Failure analysis of screw and sleeper materials under screw lateral restraint tests. Damage progress for screw bending, fibre shear-out, and plastic bearing. FEA model to demonstrate stress distribution in screw and sleeper materials. Correlation of the lateral restraint behaviour with the sleeper's material strength. FEA simulation of the lateral force in railway sleepers. Abstract: Broken spikes/screws were reported to fail in bending at the sleeper hole due to repeated lateral force and have become a major challenge for hardwood timber sleepers. The emergence of polymeric based composite railway sleepers further highlighted this problem as they are perceived to have limited screw lateral restraint. It is thus significant to evaluate the lateral restraint behaviour of timber and the timber replacement composite sleepers. This study investigated the lateral strength of timber, synthetic composite and Ultra High Molecular Weight Polyethylene plastic sleepers at the standard required displacement of 5.1 mm as suggested by the American Railway Engineering and Maintenance-of-way Association and up to failure. The results showed screw yielding and sleeper material hardening even before 5.1 mm displacement while timber and synthetic composites exhibited ultimate lateral strength almost half of plastics' performance due to the relatively weak shear capacity in the fibre direction. The grain/fibre shear-out failure was noticed in the orthotropic sleeper materials (timber and synthetic composites) while the isotropic material (plastic) mainly exhibited bearing failure. Based on the isotropic hardening rule and Hill's criterion, the developed finite element models predicted very well the screw lateral deformation and strength of timber and composite sleepers.